Enhancing the Dimensions of Student Religiosity Trough Baitul Arqam Program - Afifi, Zaki; Miswala, Sakana Tiswi; Tirta, Kania Dewi; Prastowo, Agung Ilham (Jurnal Pendidikan Islam, 2025)
Religiosity-related issues among university students such as a lack of interest in reading the Qur'an, neglect of prayer, and engagement in deviant behaviour remain prevalent. Although various efforts have been made, studies that comprehensively examine the enhancement of religiosity based on its multidimensional aspects are still limited. This study aims to explore how the Baitul Arqam program at Universitas Muhammadiyah Surakarta contributes to strengthening the five dimensions of student religiosity. Using a descriptive qualitative approach and a case study design, data were collected through in-depth interviews, direct observation, and document analysis. The findings reveal that the program systematically enhances the ideological, ritualistic, intellectual, experiential, and consequential dimensions through the deepening of Islamic teachings, habituation of worship practices, and the creation of a spiritually supportive environment. These findings provide empirical evidence of the program’s effectiveness in enhancing student religiosity and serve as a reference for developing religious training programs in other Islamic higher education institutions.